2007
DOI: 10.1186/1471-2407-7-97
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Akt is increased in the dysplasia-carcinoma sequence in Barrett's oesophagus and contributes to increased proliferation and inhibition of apoptosis: a histopathological and functional study

Abstract: BackgroundThe incidence of oesophageal adenocarcinoma is increasing rapidly in the developed world. The serine-threonine protein kinase and proto-oncogene Akt has been reported to regulate proliferation and apoptosis in several tissues but there are no data on the involvement of Akt in oesophageal carcinogenesis. Therefore we have examined the activation of Akt in Barrett's oesophagus and oesophageal adenocarcinoma and the functional effects of Akt activation in vitro.MethodsExpression of total and active (pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…Although this requires further investigations, these results raise the possibility that one or more signalling cascades becomes increasingly disrupted during cancer progression [36,37], resulting in a reduced sensitivity to PA exposure. Data presented here demonstrate for the first time that procyanidins can alter the cell cycle and induce apoptosis in oesophageal cancer cells, with a direct correlation between the magnitude of the effect and the degree of polymerization of the flavan-3-ols applied, and suggesting a mechanism whereby polymeric PA may have the potential to affect the development of OA.…”
Section: G1mentioning
confidence: 84%
“…Although this requires further investigations, these results raise the possibility that one or more signalling cascades becomes increasingly disrupted during cancer progression [36,37], resulting in a reduced sensitivity to PA exposure. Data presented here demonstrate for the first time that procyanidins can alter the cell cycle and induce apoptosis in oesophageal cancer cells, with a direct correlation between the magnitude of the effect and the degree of polymerization of the flavan-3-ols applied, and suggesting a mechanism whereby polymeric PA may have the potential to affect the development of OA.…”
Section: G1mentioning
confidence: 84%
“…Moreover, constituents of gastroesophageal refluxate, i.e., acid and bile acids modulate Barrett's cell proliferation and apoptosis increasing substantially the risk for EA [17,19]. We and others have previously pointed out the role of acid and bile acids to increase cell proliferation and survival in Barrett's cell line by up-regulating MAPK and PI3k/Akt signals [20][21][22][23][24][25][26][27]. The concomitant inductions of cyclin D1 and cyclin E in response to theses agents drive cell cycle progression through G1 to S transition [28][29][30].…”
Section: Introductionmentioning
confidence: 95%
“…In vitro analysis has revealed that only CGA and MKN28 cancer cells demonstrated upregulation of pAKT in response to brief NO exposure. In Barrett's esophagus, activation of AKT is associated with dysplasia-carcinoma sequence (39). In addition, only CGA has been found to express hTERT (13).…”
Section: Telomeres and Aktmentioning
confidence: 99%